Applications of Monte-Carlo simulation and chemometric techniques for development of bioanalytical liquid chromatography method for estimation of rosuvastatin calcium. Issue 18 (8th November 2017) - Beg, Sarwar; Panda, Sagar Suman; Katare, O. P.; Singh, Bhupinder
ABSTRACT: In the present work, we investigated the development of a bioanalytical HPLC method of rosuvastatin (RSV) calcium as per the Quality by Design (QbD)-based systematic chemometric tools. At first, the method objectives were framed and critical analytical attributes (CAAs) were chosen. Risk assessment and factor screening was performed using Hybrid Risk Matrix and Plackett–Burman design for identifying vital factors influencing the critical method parameters (CMPs). Monte-Carlo simulation analysis was conducted which confirmed excellent process robustness (Ppk >1.33) for the studied ranges of CMPs. Furthermore, systematic method development was carried out using custom experimental design, where mobile phase ratio, pH, and injection volume were taken as CMPs at three levels. The obtained trials were evaluated for peak area, retention time, theoretical plates, and peak tailing as CAAs. Mathematical response surface modeling was carried out and optimal chromatographic solution was identified using response optimizer plots. Method transfer was made to bioanalytical scale for estimation of the analyte in rat plasma samples. Extensive method validation was performed as per the ICH Q2 guideline, which indicated validation parameters within the acceptable limits. Overall, the studies construed successful development of QbD compliant HPLC method of rosuvastatin with potential utility bioanalytical testing. GRAPHICAL ABSTRACT: